Performance-Based Teacher Evaluation in Indonesian Public and Private Madrasah Tsanawiyah: A Qualitative Comparative Case Study - Nur Afif; Akhmad Shunhaji; Khasnah Syaidah (STAI Hubbulwathan Duri, 2026)
Teacher performance evaluation is central to educational quality assurance; however, within Islamic educational institutions it must also address moral and spiritual dimensions. This study examines how teacher performance evaluation is conceptualized and implemented in public and private Madrasah Tsanawiyah, and how institutional governance shapes its developmental impact. Adopting a qualitative comparative case study design, the research was conducted in two Islamic junior secondary schools in South Jakarta, one public and one private madrasah. Data were generated through in-depth interviews with principals, teachers, and community representatives, focus group discussions, classroom and supervision observations, and document analysis. Using cross-case thematic analysis and pattern matching, the study reveals contrasting evaluation logics: a regulation-driven, accountability-oriented model in public madrasahs and a flexible, value-integrative model in private madrasahs. While standardized systems enhance administrative consistency, value-based and dialogical evaluation practices demonstrate stronger alignment with professional development, instructional improvement, and teachers’ role as moral exemplars. The findings suggest that evaluation systems in Islamic education are most effective when framed as formative and developmental rather than merely administrative. This study contributes to the literature by offering a governance-sensitive evaluation framework that integrates professional standards with Islamic ethical values, advancing a more holistic model of quality assurance in Islamic secondary education.